2017
DOI: 10.5858/arpa.2016-0616-oa
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban Causes Missed Diagnosis of Protein S Deficiency but Not of Activated Protein C Resistance (Factor V Leiden)

Abstract: - Despite rivaroxaban treatment, APCR testing can distinguish FVL-HET from normal patients, rendering indiscriminate FVL DNA testing of all patients on rivaroxaban unnecessary. Free protein S should be tested in patients taking rivaroxaban to exclude hereditary protein S deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Marked differences have been seen in PS activity results between different kits complicating the interpretation of quality assurance assessment for these assays 137 . Some DOAC have been reported to impact on the results of these assays 138 but not others 139 …”
Section: Fibrinogenmentioning
confidence: 99%
“…Marked differences have been seen in PS activity results between different kits complicating the interpretation of quality assurance assessment for these assays 137 . Some DOAC have been reported to impact on the results of these assays 138 but not others 139 …”
Section: Fibrinogenmentioning
confidence: 99%
“…12,26 DOAC may or may not falsely elevate PS activity. 26,31,32 Known conditions that interfere with PS activity and antigen tests results are listed in Table 1.…”
Section: Pre Analy Tic Al and P Os Tanaly Tic Al Variab Le S 41 | mentioning
confidence: 99%
“…Most assays are designed to reduce or eliminate the effects of vitamin K antagonist and heparin anticoagulation, whereas interference by direct‐acting anticoagulants is reagent‐dependent and drug level–dependent . Direct activated FX (FXa) inhibitors and direct thrombin inhibitors (DTIs) can falsely elevate APC‐R ratios, resulting in the potential for samples with APC‐R to be misclassified as normal, although a recent study showed that APTT‐based testing with predilution distinguished FVL heterozygotes from normal patients despite rivaroxaban treatment, even at high drug levels …”
Section: Preanalytic Issuesmentioning
confidence: 99%
“…The modified APC‐R (MAPC‐R) assay is performed identically to the CAPC‐R assay, except that plasma is diluted 1:5 in FV‐deficient plasma (FVDP) to reduce or eliminate interferences and make the assay more specific for abnormalities in FV . The FVDP eliminates interference from reduced or elevated coagulation factor levels, vitamin K antagonist therapy, low protein S levels, pregnancy, and oral contraceptives .…”
Section: Analytic Issuesmentioning
confidence: 99%